2020
DOI: 10.3892/mmr.2020.11364
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen inhalation alleviates nonalcoholic fatty liver disease in metabolic syndrome rats

Abstract: Hydrogen exhibits therapeutic and preventive effects against various diseases. The present study investigated the potential protective effect and dose-dependent manner of hydrogen inhalation on high fat and fructose diet (HFFd)-induced nonalcoholic fatty liver disease (naFld) in Sprague-dawley rats. rats were randomly divided into four groups: i) control group, regular diet/air inhalation; ii) model group, HFFd/air inhalation; iii) low hydrogen group, HFFd/4% hydrogen inhalation; and iv) high hydrogen group, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…In addition to the inhibition of JNK activation, H 2 has been shown to attenuate the activation of NF-κB in an LPS-induced cardiac dysfunction mice model ( 20 ). H 2 has also been shown to increase the hepatic expression of nuclear factor erythroid 2-related factor 2 (Nrf2) ( 42 ) and PPAR-α ( 43 ) and reduced the hepatic expression of SREBP-1c ( 44 ) in NAFLD animal models. These transcription factors are essential mediators of inflammation (NF-κB), oxidative stress (Nrf2) and lipid metabolism (SREBP-1c and PPAR-α), where they have been reported to serve key roles in the pathogenesis of both ALD and NAFLD ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibition of JNK activation, H 2 has been shown to attenuate the activation of NF-κB in an LPS-induced cardiac dysfunction mice model ( 20 ). H 2 has also been shown to increase the hepatic expression of nuclear factor erythroid 2-related factor 2 (Nrf2) ( 42 ) and PPAR-α ( 43 ) and reduced the hepatic expression of SREBP-1c ( 44 ) in NAFLD animal models. These transcription factors are essential mediators of inflammation (NF-κB), oxidative stress (Nrf2) and lipid metabolism (SREBP-1c and PPAR-α), where they have been reported to serve key roles in the pathogenesis of both ALD and NAFLD ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have since shown the therapeutic and preventive effects of H 2 in various animal disease models. 2 3 4 5 Meanwhile, some clinical investigations have also confirmed its beneficial effects on different diseases. 6 7 Various ways have been explored to administer H 2 , mainly including inhaling H 2 , drinking H 2 -rich water, injecting H 2 -rich saline, and direct incorporation of H 2 by diffusion (such as bath and eye-drops).…”
Section: Introductionmentioning
confidence: 97%
“…4 Since then, several researchers have confirmed the therapeutic and preventive effects of H 2 in various clinical trials and animal disease models. [5][6][7] H 2 therapy has been applied in aging-related diseases, such as type 2 diabetes, atherosclerosis, Parkinson's disease, and Alzheimer's disease. [6][7][8] H 2 can be administered via different routes such as H 2 gas inhalation, 5 H 2 -rich water (HRW) drinking, 9 H 2 -rich saline (HRS) injection, 10 and direct incorporation of H 2 through diffusion (such as taking H 2water bath 11 or dropping H 2 -saline into the eyes).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] H 2 therapy has been applied in aging-related diseases, such as type 2 diabetes, atherosclerosis, Parkinson's disease, and Alzheimer's disease. [6][7][8] H 2 can be administered via different routes such as H 2 gas inhalation, 5 H 2 -rich water (HRW) drinking, 9 H 2 -rich saline (HRS) injection, 10 and direct incorporation of H 2 through diffusion (such as taking H 2water bath 11 or dropping H 2 -saline into the eyes). 12 Previous studies have mainly focused on the effectiveness of H 2 administered via a specific route.…”
Section: Introductionmentioning
confidence: 99%